Heterostructure Active Area Optimization by Simulation - O.I. Rabinovich; S.I. Didenko; S.A. Legotin; I.V. Fedorchenko; U.V. Osipov (Журнал нано- та електронної фізики)
Changing LED performance characteristics, depending on Indium atoms concentration and at different temperatures were simulated. It was suggested that a LED having p-n junction area S0 can be considered as a sum of “SmallLEDs (SLEDs)” electrically connected in parallel, each SLED has its own In-content and its own p-n junction area S(X). Good correlation in simulation and experimental results has been obtained. It was determined that the best structure for AlGaInN NH is p+GaN / p+Al0.2Ga0.8N / 4(n-InxGa1 – xN-n-GaN) / n+GaN. The main thing is that in the NH AA there are 4QW-in two central ones there is maximum radiation and two ones at the both ends of active region are “barriers” which help to concentrate electrons / holes in active region and additionally “protect” QW from different defects.